2022
DOI: 10.1044/2022_aja-21-00248
|View full text |Cite
|
Sign up to set email alerts
|

Remote Monitoring of Adult Cochlear Implant Recipients Using Digits-in-Noise Self-Testing

Abstract: Purpose: The COVID-19 pandemic has accelerated the uptake and scope of telehealth. This study determined the accuracy and reliability of a smartphone digits-in-noise (DIN) test when conducted by adult cochlear implant (CI) recipients in a simulated home environment compared with a clinic setup. Perceptions of remote monitoring using speech-in-noise (SIN) testing were also explored. Method: Thirty-three adult CI recipients between 18 and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 70 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…Accurately measuring psychoacoustic thresholds outside the confines of specialized laboratories could initiate important changes in how data is collected and would increase accessibility for basic and translational research [ 4 ]. Previous studies have shown success in comparing equivalent data collected in the lab versus remotely with acoustic hearing [ 5 , 6 , 7 , 8 , 9 ] as well as with electric hearing [ 10 , 11 , 12 , 13 ]. For instance, Lelo de Larrea-Mancera et al (2022) [ 5 ] measured performance on a battery of psychoacoustic experiments in tasks involving audibility, temporal fine structure sensitivity, spectro-temproal modulation sensitivity, and spatial release from masking from a large group of young normal-hearing listeners.…”
Section: Introductionmentioning
confidence: 99%
“…Accurately measuring psychoacoustic thresholds outside the confines of specialized laboratories could initiate important changes in how data is collected and would increase accessibility for basic and translational research [ 4 ]. Previous studies have shown success in comparing equivalent data collected in the lab versus remotely with acoustic hearing [ 5 , 6 , 7 , 8 , 9 ] as well as with electric hearing [ 10 , 11 , 12 , 13 ]. For instance, Lelo de Larrea-Mancera et al (2022) [ 5 ] measured performance on a battery of psychoacoustic experiments in tasks involving audibility, temporal fine structure sensitivity, spectro-temproal modulation sensitivity, and spatial release from masking from a large group of young normal-hearing listeners.…”
Section: Introductionmentioning
confidence: 99%